RESTORE Survey on the Public Perception of Advanced Therapies and ATMPs in Europe—Why the European Union Should Invest More! - Goldsobel, Gady; von Herrath, Christoph; Schlickeiser, Stephan; Brindle, Nicola; Stähler, Frauke; Reinke, Petra; Aberman, Zami; Ofir, Racheli; Dessole, Gabriella; Benvenuti, Stefano; Neves, Nuno M.; Reis, Rui L.; et al. (Frontiers in Medicine, 2021)
Advanced therapy medicinal products (ATMPs) are potential game changers in modern medical care with an anticipated major impact for patients and society. They are a new drug class often referred to as “living drugs”, and are based on complex components such as vectors, cells and even tissues. The production of such ATMPs involves innovative biotechnological methods. In this survey, we have assessed the perception of European citizens regarding ATMPs and health care in Europe, in relation to other important topics, such as safety and security, data protection, climate friendly energy supply, migration and others. A crucial question was to determine to what extent European citizens wish to support public funding of innovations in healthcare and reimbursement strategies for ATMPs. To answer this, we conducted an online survey in 13 European countries (representative of 85,3% of the entire EU population including the UK in 2020), surveying a total of 7062 European citizens. The survey was representative with respect to adult age groups and gender in each country. Healthcare had the highest ranking among important societal topics. We found that 83% of the surveyed EU citizens were in support of more public funding of technologies in the field of ATMPs. Interestingly, 74% of respondents are in support of cross-border healthcare for patients with rare diseases to receive ATMP treatments and 61% support the reimbursement of very expensive ATMPs within the European health care system despite the current lack of long-term efficacy data. In conclusion, healthcare is a top ranking issue for European Citizens, who additionally support funding of new technologies to enable the wider application of ATMPs in Europe.